A mídia e a construção do medo social : um estudo da imprensa em Cuiabá - Lessa, Maria de Fátima Pereira (2017)
This study aims to contribute to the reflection on the role of negative / sensationalist news in local media in the construction of social fear. The proposal is to deal with journalism in its various facets, with very different forms, methods and objectives, according to the purposes of the producer and the audience for which it is intended. Our core think tank will be local printed commercial media. For its accomplishment, analytical references were sought in Marxist authors on the press relation and the bourgeois thought. This research was defined as documentary, for which we chose as sources two newspapers of daily circulation, A Gazeta and Diário de Cuiabá, demarcating as study period the year 2016. For the analysis of the news, the historical-dialectical method was used. It is not an exhaustive text about the theory of journalism nor about fear, since the pretension was to underline some aspects that provided us with elements for the formulation of the objectives and variables that made it possible to evaluate if the news published in the local media collaborate in the construction of the social fear.